Applying a Low Cost, Mini Remotely Operated Vehicle (ROV) to Assess an Ecological Baseline of an Indigenous Seascape in Canada - Buscher, Elena; Mathews, Darcy L.; Bryce, Cheryl; Bryce, Kathleen; Joseph, Darlene; Ban, Natalie C. (Frontiers in Marine Science, 2020)
Marine ecosystems are facing unprecedented threats. Baseline information about the state of ecosystems is needed to address these threats. Ecosystem assessments can be completed over varying scales through different methodologies or a combination of them. Despite these many technologies, most marine environments lack comprehensive habitat assessments. Remotely operated vehicles (ROVs) provide an opportunity to conduct small- to meso scale ecological surveying without some of the constraints of commonly used methodologies such as scuba. The development of cost-effective models of ROVs broadens the accessibility of this technology to many different user groups. We applied the Trident ROV as part of a community-based research project to conduct marine conservation planning around the Tl’ches archipelago with the Songhees Nation in Victoria, British Columbia. We had two main objectives: (1) We evaluated the marine ecological data collection capabilities for the Trident OpenROV and (2) our surveys aimed to complete a systematic benthos classification and document the algal community as well as document a baseline of Songhees culturally important species. We also discuss evaluated the ability of the Trident to provide high resolution ecological data to inform a marine use planning process. We found the Trident to be a capable tool to conduct systematic marine surveying despite some limitations such as low maneuverability in moderate to high current environments and dense kelp areas. We were able to document 14 of 25 culturally important species and 28 species of algae and seaweeds. We were also able to identify highly stressed environments suited for future restoration efforts. The application of a mini low cost ROV to inform marine use planning generated high-resolution data that enabled the Songhees Nation to confirm the whole archipelago warrants protection and necessitates the exclusion of non-Indigenous user groups. Documenting and having a permanent record of the substrate, algal cover, and culturally important species composition around the seascape Tl’ches could serve as one reference point for the Songhees Nation to establish a monitoring system.